(Invited) Bio-Derived Binders for More Sustainable Cobalt-Free Lithium Battery Cathodes - Binder, Markus; Bresser, Dominic (Meeting abstracts (Electrochemical Society), 2025)
Lithium-ion batteries have enabled the transition from gasoline-powered vehicles to electric vehicles (EVs) and the increase in EV sales has risen almost exponentially in the past few years. This impressive success, however, raises also an increasing awareness of sustainability issues – not least with regard to critical elements such as cobalt, commonly comprised in the positive electrode active material, and the use of toxic and harmful solvents for the (positive) electrode preparation. [1–3] Cobalt-free and manganese-rich LiNi 0.5 Mn 1.5 O 4 (LNMO) would provide a viable solution to overcome these issues, especially in combination with the utilization of water-soluble, bio-derived polymers as binders, but the pronounced water-sensitivity and high de-/lithiation potential of LNMO are still hampering the commercial breakthrough. [3–5] Apparently, the key towards overcoming these issues relies on the stabilization of the LNMO|water and LNMO|electrolyte interface, while also the realization of high active material mass loading electrodes provides a great challenge towards the commercialization of such binders. Herein, a comprehensive overview of our activities in this field will be provided, focusing on (i) an in-depth understanding of the processes occurring at the interface with the LNMO particles, (ii) the development of suitable active material and electrode treatments prior to the cell assembly, and (iii) the tailored design of suitable binder compositions that allow for suitable mechanical properties and stable long-term cycling of commercially relevant sized electrodes – in half-cells and graphite║LNMO full-cells. References [1] E. A. Olivetti, G. Ceder, G. G. Gaustad, X. Fu, Joule 2017 , 1 , 229. [2] C. Vaalma, D. Buchholz, M. Weil, S. Passerini, Nature Reviews Materials 2018 , 3 , 18013. [3] D. Bresser, D. Buchholz, A. Moretti, A. Varzi, S. Passerini, Energy Environ. Sci. 2018 , 11 , 3096. [4] B. Aktekin, M. J. Lacey, T. Nordh, R. Younesi, C. Tengstedt, W. Zipprich, D. Brandell, K. Edström, The Journal of Physical Chemistry C 2018 , 122 , 11234. [5] M. Wentker, M. Greenwood, J. Leker, Energies 2019 , 12 , 504.